Investigating potential biochemical properties of fetal membrane spongy layer for clinical application at the ocular surface - Lazutina, Elena (2017)
The amniotic membrane, well known scaffolding tissue, which widely uses and benefits of having anti-inflammatory, anti-microbial, anti-fibrosis, anti-scarring with low immunogenicity and reasonable mechanical properties. Amniotic Membrane Transplantation (AMT) is an established treatment modality, which favourably influence ocular surface re-epithelisation and prevents angiogenesis, thus promoting healing and minimising scarring. It is also used at several other sites of the body. Despite its widespread use, key elements of the membrane and its precise mechanism(s) of action remain to be elucidated. Unfortunately, over the years conflicting clinical reports have suggested variations in the efficacy of AM utility. Conventional methods for amnion preparation do not acknowledge the presence of the SL.